Chromium catalysts based on PNP(NR2)2 ligands for selective ethylene oligomerization. (23rd September 2021) - Zhang, Jingyi; Alam, Fakhre; Fan, Haonan; Ma, Jing; Jiang, Tao
Abstract : High active and selective 1–3 chromium catalysts based on the corresponding Ph2 PN(cyclopentyl)P (NR2 )2 ‐type L 1 –L 3 ligands (L 1 : R = methyl, L 2 : R = ethyl, L 3 : R = isopropyl) have been explored for selective ethylene tri‐/tetramerization. We found that the ligand substituents and the experimental conditions considerably influenced the catalytic performance of 1–3 based catalysts. Combining a higher ethylene pressure can elevate the selectivity of 1‐octene (67.98%) of precatalyst 1 with high catalytic activity (9.3 × 10 6 g/[molCr h]). Furthermore, precatalysts 2–3 efficiently offer selective ethylene trimerization and afforded 97.76% 1‐hexene selectivity with 5.8 × 10 6 g/(molCr h) catalytic activity (in case precatalyst 3 ). A relatively low catalyst mass, high Al/Cr molar ratio, and high ethylene pressure display excellent catalytic activity and selectivity for ethylene oligomerization. Abstract : The chromium 1 –3 complexes of the corresponding Ph2 PN(cyclopentyl)P (NR2 )2 ‐type L 1 –L 3 ligands (L 1 : R = methyl, L 2 : R = ethyl, L 3 : R = isopropyl) when activated with MMAO‐3A cocatalyst afforded efficient catalysts for selective ethylene tri‐/tetramerization. The distribution of products showed that these systems have a significant impact on their catalytic performance in ethylene oligomerization. Precatalyst 1 exhibited 67.98% selectivity toward 1‐octene, whereas precatalysts 2 –3 afforded 97.76% high selectivity 1‐hexene selectivity with significantly high catalytic activity.